Immature Gastric Teratoma in a Newborn: A Case Report - Kumar, Sanjay (J Neonatal Surg, 2016)
A case of immature gastric teratoma in a neonate is being reported here. The neonate was presented with abdominal mass and distension and managed with excision of mass; the patient is doing fine postoperatively.